2012
DOI: 10.7166/23-3-507
|View full text |Cite
|
Sign up to set email alerts
|

Project Management Maturity and Project Management Success in the Engineering and Construction Industries in Southern Africa

Abstract: Previous studies have attempted to determine how the success of South African IT projects related to the project management maturity of the organisations that executed the projects. The study reported in this article was conducted during 2010 in the engineering and construction sectors. This paper reports on a structured questionnaire distributed to 1,625 individuals mainly in the South African engineering and construction industries, from which 255 responses were received. 'Project success' was self-defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 12 publications
2
32
3
1
Order By: Relevance
“…Labuschagne, Marnewick and Jakovljevic (2008) investigated IT management maturity in SA and discovered that IT project maturity has improved, but IT projects continue to fail. Similar results are seen in Bogopa (2010) and Pretorius, Steyn and Jordaan (2012). Only three studies focusing on KM were found.…”
Section: Knowledge Management Practices In Software Organisationssupporting
confidence: 73%
“…Labuschagne, Marnewick and Jakovljevic (2008) investigated IT management maturity in SA and discovered that IT project maturity has improved, but IT projects continue to fail. Similar results are seen in Bogopa (2010) and Pretorius, Steyn and Jordaan (2012). Only three studies focusing on KM were found.…”
Section: Knowledge Management Practices In Software Organisationssupporting
confidence: 73%
“…Despite all this international research, research in PMM seems to be neglected in the South African context. The last couple of years have seen the publication of a small amount of research [9] [10]. This research has provided PMM benchmarks in the engineering and construction industries as well as an African perspective of PMM across all industries.…”
Section: Introductionmentioning
confidence: 99%
“…According to Saures, cited in Skulmoski [17], increased maturity indicates the increased importance of project management to an organisation. Even though an increase in maturity will not guarantee project success [13,18], it should improve the chances of project success [19]. It is also an indication of an increase in the number of support systems that are in place to aid a project.…”
Section: Research Question 5: What Value Is Added By the Pmo?mentioning
confidence: 99%